Tumor Lipids of Pediatric Papillary Renal Cell Carcinoma Stimulate Unconventional T Cells - Lehmann, Nadine; Paret, Claudia; El Malki, Khalifa; Russo, Alexandra; Neu, Marie Astrid; Wingerter, Arthur; Seidmann, Larissa; Foersch, Sebastian; Ziegler, Nicole; Roth, Lea; Backes, Nora; Sandhoff, Roger; et al. (Frontiers in Immunology, 2020)
Papillary renal cell carcinoma (PRCC) is a rare entity in children with no established therapy protocols for advanced diseases. Immunotherapy is emerging as an important therapeutic tool for childhood cancer. Tumor cells can be recognized and killed by conventional and unconventional T cells. Unconventional T cells are able to recognize lipid antigens presented via CD1 molecules independently from major histocompatibility complex, which offers new alternatives for cancer immunotherapies. The nature of those lipids is largely unknown and α-galactosylceramide is currently used as a synthetic model antigen. In this work, we analyzed infiltrating lymphocytes of two pediatric PRCCs using flow cytometry, immunohistochemistry and qRT-PCR. Moreover, we analyzed the CD1d expression within both tumors. Tumor lipids of PRCC samples and three normal kidney samples were fractionated and the recognition of tumor own lipid fractions by unconventional T cells was analyzed in an in vitro assay. We identified infiltrating lymphocytes including γδ T cells and iNKT cells, as well as CD1d expression in both samples. One lipid fraction, containing ceramides and monoacylglycerides amongst others, was able to induce the proliferation of iNKT cells isolated from peripheral blood mononuclear cells (PBMCs) of healthy donors and of one matched PRCC patient. Furthermore, CD1d tetramer stainings revealed that a subset of iNKT cells is able to bind lipids being present in fraction 2 via CD1d. We conclude that PRCC are infiltrated by conventional and unconventional T cells and express CD1d. Moreover, certain lipids, present in pediatric PRCC, are able to stimulate unconventional T cells. Manipulating these lipids and T cells may open new strategies for therapy of pediatric PRCCs.